A Molecular Subtype Model for Liver HBV-Related Hepatocellular Carcinoma Patients Based on Immune-Related Genes - Zhang, Qiyao; Yu, Xiao; Zheng, Qingyuan; He, Yuting; Guo, Wenzhi (Frontiers in Oncology, 2020)
Hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC) is one of the most common malignant tumors in the world with a very poor prognosis. Immunotyping is of great significance for predicting HCC outcomes and guiding immunotherapy. Therefore, we sought to establish a reliable prognostic model for HBV-related HCC based on immune scores. We identified immune-related modules of TCGA-LIHC and GSE14520 datasets through weighted gene co-expression network analysis (WGCNA), and evaluated HCC through a non-negative matrix factorization (NMF) algorithm. Through further bioinformatics analyses, we identified causes for prognostic differences between subtypes. The results illustrate a significant difference in prognosis based on immunotypes, which may stem from metabolic disorders and increased tumor invasion associated with the high expression of genes related to stem cell characteristics. In conclusion, our model provides a reliable prognostication method towards personalized immunotherapy for HBV-related HCC.